Surface Texture Manufacturing Techniques and Tribological Effect of Surface Texturing on Cutting Tool Performance: A Review. Issue 6 (1st November 2016) - Arslan, A.; Masjuki, H. H.; Kalam, M. A.; Varman, M.; Mufti, R. A.; Mosarof, M. H.; Khuong, L. S.; Quazi, M. M.
ABSTRACT: The tribological characteristics of sliding surfaces have been remarkably improved by surface texturing. Surface texturing can be beneficial in many ways; for example, it can reduce friction and wear, increase load carrying capacity, and increase fluid film stiffness. The design process for surface texturing is highly correlated to the particular functions of any application for which texturing is required. Texture quality is greatly affected by manufacturing methods, therefore, it is important to have a detailed understanding of the related parameters of any technique. The use of surface texturing to improve the cutting performance of tools is a relatively new application. These textures improve cutting performance by enhancing lubricant availability at the contact point, reducing the tool-chip contact area, and trapping wear debris. Reductions in crater and flank wear, friction force, cutting forces, and cutting temperature are the main benefits obtained by this technique. To date, surface texturing has been successfully used in drilling, milling, and turning operations. This article provides an overview of the techniques that have been used in industry and research platforms to manufacture micro-/nano-textures for tribological applications, and it examines the effects of surface textures on cutting tool performance.